Mgtricity business plan - market analysis - Fernandes, Mariana De Prates Batista (2020)
A global energy markets overview is presented with a deeper look into the sub- saharan Africa region. Three countries are taken into account and from those one is chosen as the market entry for MGtricity. Moreover, stakeholders, direct competitors and market barriers are also considered and presented in the analysis.